There Is More than One Way to Do It: Fostering an Interdisciplinary Approach to the Politics of Sexuality - D’Amico, Cristina (The Oracle, 2021)
In this paper, I engage with Michel Foucault’s philosophy of sexuality, specifically the discursive method articulated in The History of Sexuality, Vol.1. Drawing primarily from the work of Sigmund Freud (1905), Antonio Gramsci (1931), Ian Craib (1997), as well as prominent York University scholars John O’Neill (1995) and Loree Erikson (2000), the paper uncovers some of the politically debilitating philosophical assumptions on which Foucault’s work is predicated, and which prevent his text (as well as other postmodern theories of sexuality) from producing a radical, inclusive and liberating politics of sexuality. The paper does not seek to discredit the validity, utility or profundity of Foucault’s constructionist theories — rather, the main objective of the essay is to encourage psychoanalytic, social constructionist, historical and scientific approaches to sexual theory. I suggest that to understand the complex phenomenon of sexuality and promote an inclusive, radical politics of sexuality, theorists need to approach the study of sexuality from multiple perspectives.